Трибологические испытания и физическая модель истирания углеродных материалов в окислительной среде при высоких температурах и ионизирующем излучении - Комир, Антон Игоревич; Одейчук, Николай Петрович; Ткаченко, Виктор Иванович (НТУ "ХПИ", 2018)
Для анализа пылеобразования при истирании однотипных углеродных материалов выполнены их трибологические испытания при температурах 400-600 °C в окислительной среде под воздействием ионизирующего излучения. Показано, что скорость увеличения массы порошка графита в логарифмическом масштабе пропорциональна температуре испытаний. Определено, что при температурах испытаний и под воздействием электронного пучка графиты марки МПГ подвержены истиранию в большей степени, чем графиты марок АРВ, ГСП, УУКМ. Установлено, что для пор диаметром порядка микрона износ меньше, чем для наноразмерных пор. Показано, что для наноразмерных пор истираемость пропорциональна их размеру. Предложена физическая модель истирания углеродных материалов.

In this paper, we describe the tribological tests of carbon materials at high temperatures (400-600 °C), in an oxidizing medium and under the influence of ionizing radiation. The aim of the study is to analyze the dust formation during erasing of the same type of graphite samples. In experiments used the method developed earlier, a rapid analysis of the dependence of the change in mass of graphite powder on attrition time was carried out. It is shown that, on a logarithmic scale, the rate of change in mass of the graphite powder can be considered as linear dependence on temperature. It has been experimentally determined that with increase of experiments temperature, and under the influence of the electron beam, the graphite of MPG grade is most vulnerable to erasing wear. Grades of graphite ARV, GSP, UUKM have less wear compared to grade of graphite MPG. It is concluded that for pores of large diameters (of the order of a micron) wear is less than for nanoscale pores. It is shown that in nano-sized range of pores the smaller the pore size, the less the erasing. On the basis of the experimental data obtained, a physical model is proposed for describing the time dynamics of reactor graphites erasing at different temperatures and under the influence of an electron beam. The physical model of nuclear graphite erasing is based on a simplified scheme of reactor graphite attrition process, which considers the process of destruction of graphites in contact boundary layer with a thickness of order of the double mean diameter of the prevailing pores. Under the assumption of an insignificant change in temperature as a result of friction, as well as the effect of an electron beam, an equation for the change in the mass of the graphite powder in time is obtained.
Tribolical tests and physical model of erasing of carbon materials in the oxidative medium at high temperatures and ionizing radiation
Keywords: ядерный графит; окисление; электронные пучки; высокая температура; nuclear graphite; electron beams